Efecto de un programa de inteligencia emocional, en el desarrollo del aprendizaje significativo de los estudiantes del 4to. grado de Educación secundaria de la IEP. Sagrado Corazón de Jesús, Distrito de Chao - Virú, 2017 - Jaramillo Yupanqui, Nelly Teresa (2018)
ABSTRACT The main objective was to establish the effect of the application of an Emotional Intelligence Program, in the development of significant learning of the students of the 4th. degree of secondary education of the IEP. "Sacred Heart of Jesus", district of Chao-Virú, 2017. The quasi-experimental design of 2 groups with pre and post test application was used, for which a sample of 40 children divided into 2 groups was selected (Control section "A" and experimental section "B"). The experimental proposal consisted of a set of work sessions in which didactic strategies of emotional intelligence were implemented, in which the significant learning of the children was promoted, in a period of 4 months. After applying the pre and posttest of significant learning, it was determined that in the pretest, both groups in 70% were in a low level; However, after applying the emotional intelligence program, the students in the experimental group reached a high level of 70% and, conversely, the control group remained at the low level by 60%. Likewise, the hypothesis test of the difference in means allowed to establish that the mean of the experimental group was significantly greater than that of the control group, since the p value was p = 0.000.